Resolução de problemas de congruência de triângulos com auxílio do software Geogebra - Vasconcelos, Francisco Ricardo Nogueira de (2015)
Our challenge as a teacher is to enable the improvement of education quality in mathematics looking for ways to ensure the formation of citizens able to recognize their role in society and find illuminating paths to the performance of a promising career. In this sense, we seek to focus our research on pedagogical actions which enable the development of the students cognitive potential. For this, we propose the use of GeoGebra software as a teaching tool for Plane Geometry classes, because we believe that this resource provides a favorable environment for the development of learning to the student and places the teacher as a mediator in the process of conceptual systematization of the necessary mathematical ideas to the development of the students cognitive structures. The aim of our study is to support the students of degree in Mathematics from the Federal Institute of Education, Science and Technology in order to use GeoGebra software as a teaching tool to help solving plane geometry problems involving cases of congruence triangles. For analysis and data collection, it was carried out the study of the pedagogical project of the course and the completion of a short course for the use of GeoGebra software designed for 21 students enrolled in plane geometry discipline.We used as research tools two diagnostic questionnaires, observation and photographic record. Analysis of the results showed that students in the degree course were receptive to the use of GeoGebra software in the classroom, and the short course and teaching activities applied had a great level of acceptance by the future teachers of mathematics.The conclusions point out that the use of GeoGebra software should be understood as an alternative teaching tool for teaching Geometry in order to provide the student a dynamic, interactive and fun method for learning mathematics.